Genetic diagnosis of fetal microcephaly at a single tertiary center in China - Wang, You; Fu, Fang; Lei, Tingying; Zhen, Li; Deng, Qiong; Zhou, Hang; Ma, Chunling; Cheng, Ken; Huang, Ruibin; Li, Ru; Yu, Qiuxia; Li, Lushan; et al. (Frontiers in Genetics, 2023)
Background: Microcephaly is common in patients with neuropsychiatric problems, and it is usually closely related to genetic causes. However, studies on chromosomal abnormalities and single-gene disorders associated with fetal microcephaly are limited. Objective: We investigated the cytogenetic and monogenic risks of fetal microcephaly and evaluated their pregnancy outcomes. Methods: We performed a clinical evaluation, high-resolution chromosomal microarray analysis (CMA), and trio exome sequencing (ES) on 224 fetuses with prenatal microcephaly and closely followed the pregnancy outcome and prognosis. Results: Among 224 cases of prenatal fetal microcephaly, the diagnosis rate was 3.74% (7/187) for CMA and 19.14% (31/162) for trio-ES. Exome sequencing identified 31 pathogenic or likely pathogenic (P/LP) single nucleotide variants (SNVs) in 25 genes associated with fetal structural abnormalities in 37 microcephaly fetuses; 19 (61.29%) of which occurred de novo. Variants of unknown significance (VUS) was found in 33/162 (20.3%) fetuses. The gene variant involved included the single gene MPCH 2 and MPCH 11, which is associated with human microcephaly, and HDAC8, TUBGCP6, NIPBL, FANCI, PDHA1, UBE3A, CASK, TUBB2A, PEX1, PPFIBP1, KNL1, SLC26A4, SKIV2L, COL1A2, EBP, ANKRD11, MYO18B, OSGEP, ZEB2, TRIO, CLCN5, CASK, and LAGE3. The live birth rate of fetal microcephaly in the syndromic microcephaly group was significantly higher than that in the primary microcephaly group [62.9% (117/186) vs 31.56% (12/38), p = 0.000]. Conclusion: We conducted a prenatal study by conducting CMA and ES for the genetic analysis of fetal microcephaly cases. CMA and ES had a high diagnostic rate for the genetic causes of fetal microcephaly cases. In this study, we also identified 14 novel variants, which expanded the disease spectrum of microcephaly-related genes.